(untitled) (Latakia University Journal -Engineering Sciences Series, 2019)
تتعرّض الشبكة الكهربائية لتوترات زائدة داخلية، وخارجية، مما يعرّضها للخطر لعدم إمكانية تصميم عازليتها من وجهة النظر الاقتصادية لتتحمّل جميع هذه التوترات. لذلك لا بد من القيام بإجراءات إضافية لحماية التجهيزات عند تعرّضها لتلك التوترات، ويتم ذلك باستخدام مفرّغات التوتر في شبكات التوتر المتوسط، لعدم إمكانية الاعتماد على الخط الأرضي (خط مرس الحماية) المعلّق في أعلى أبراج التوتر كحماية إضافية كما هو الحال في شبكات التوتر العالي، وذلك لصِغَر المسافة بين الخط الأرضي والأطوار، مما يؤدي إلى حدوث قفزة بينها عند إصابة الخط الأرضي إصابة مباشرة بصاعقة. فقد بيّنت إحصاءات الأعطال في مشتركي كهرباء اللاذقية وطرطوس أن 80% من الأعطال في هذه الشبكات تسبّبها التوترات الزائدة الناتجة عن الصواعق. يهدف هذا البحث إلى تحديد آلية الاختيار الصحيح لنوع المفرّغات، والاختبارات المطلوبة لها من قبل المصنع والمستثمر قبل وضعها في الخدمة، وكيفية تركيبها بشكل صحيح. كما يهدف إلى دراسة تأثير نوع البرج الحامل للشبكة الهوائية، وذلك للحدّ من أعطال محولات القدرة 20/0.4 kV في شبكات التوتر المتوسط. استناداً إلى ما سبق تم في هذا البحث اقتراح طريقة بسيطة لاختبار مفرغات التوتر المركّبة في شبكة التوتر المتوسط كل فترة زمنية، عن طريق قياس تيار التسرب في المقاومات الفحمية، ومقارنة ذلك مع القيم المسموحة. The electric network is subject to internal and external excess voltage, which makes it prone to danger because there is no possibility of economically designing its insulation to undergo these voltages. Therefore, we must make additional arrangements to protect the equipment when subjected to these voltages; this can be done by using voltage arrestor in medium voltage networks, because we cannot use the earthing line hanging on top of the towers as additional protection, as is the case in high voltage networks; because of the short distance between the earthing line and phases, this triggers a stroke between them when the earthing line is directly subjected to a thunderbolt. The statistics of fault in customers of Lattakia and Tartous electricity company has shown that 80% of faults in these networks is caused by excess voltages resulting from thunderbolts. This research aims to determine the correct selection of the type of arrestors and the necessary tests performed by the manufacture and customer before being used. This study also aims to examine the effect of the type of tower used in overhead networks on reducing the faults of power transformers (20/0.4 kV) in medium voltage networks. In this research, a simple approach has been suggested for testing the voltage arrestor used in medium voltage networks for each period of time by measuring the leakage current in carbon resistors and comparing it with allowable values.